ANALISIS PENYEBAB MOTIVASI YANG RENDAH DALAM PEMBELAJARAN BAHASA ARAB DI PONDOK PESANTREN AL MA'ARIF - Pratama, Andy Riski (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2023)
This article discusses the challenges in learning Arabic at the Alma'arif Islamic Boarding School, especially regarding the lack of student motivation. Arabic is considered important in the context of understanding the Koran and Hadith, as well as an integral part of Islamic educational institutions in Indonesia. Despite this, many students face difficulties in motivating themselves to learn Arabic. The research method used is descriptive qualitative, with a focus on student motivation in learning Arabic. The research results show that student motivation varies, influenced by intrinsic and extrinsic factors, as well as internal and external conditions. Students with high motivation show high enthusiasm and involvement, while students with low motivation tend to lack focus and do not complete assignments on time. Analysis causes a lack of student motivation in identifying several factors, including monotonous teaching methods, lack of relevance of material, conditions of facilities and learning environment that are not conducive, as well as lack of support and understanding from the teacher. Apart from that, the absence of awards and recognition for student achievements is also considered a factor in reducing motivation.